Mengapa Pendapatan Asli Daerah (PAD) Kabupaten/Kota Relatif Rendah? - Rahainah Anggrayani; Muhammad Handry Imansyah (PPJP Universitas Lambung Mangkurat, 2022)
The goal of this researchis determine the contribution of GRDP, Population, Retribution and Taxes to PAD. The analytical method used is panel data regression with classical assumption testing. The outcome of the multicollinearity test is, there is no multicollinearity variables in the model. The results of the heteroscedasticity test as a whole are independent variables in the regression model free from heteroscedasticity problems. Results of autocorrelation test show that regression model value does not contain autocorrelation. Based on the results of the GRDP Regression test, Population, Taxes and Regional Retribution have a positive and significant influence on Regional Income. Based on the results of the F test there is a significant effect between all variables simultaneously on (Y). While the outcome of the t-test show that GDP, taxes and regional retribution have a significant effect on PAD. While the population has no significant effect.